Cahaya Lilin dalam Karya Seni Lukis Simbolik - Prasetyo, Teguh; Fitryona, Nessya (Lembaga Yasin AlSys, 2025)
This study explores the concept of a mother’s love through symbolic painting, using candlelight as the central symbol. The creative process was carried out systematically through the stages of preparation, elaboration, synthesis, and artwork production. The idea was developed from observations, art literature reviews, and personal experience, then focused on the theme of maternal affection. In the elaboration stage, the core idea was expanded using additional references to design an aesthetically compelling composition, while the synthesis stage emphasized conceptual development based on visual art principles to convey deeper meaning. The creation process involved sketching, selecting tools and materials, transferring sketches onto canvas, and painting with acrylics. The finishing stage included final touches and feedback from a supervisor, culminating in an art exhibition. The resulting artworks employ candlelight as a symbol of a mother’s love and sacrifice in nurturing her child. Through titles such as